Supportive supervision of village, health, sanitation and nutrition day (VHSND) during post-pandemic period in Assam - Mahanta, Tulika Goswami; Saikia, Mridushman; Baruah, Swarnali D; Ranghonpi, Padmashree (Indian Journal of Community Health, 2024)
Background: VHSND, a community platform bringing health, early childhood development, nutrition, and sanitation services by community engagement was affected by COVID-19 pandemic. Aims & Objectives: To assess the process of VHSND implementation during post-pandemic period in Assam. Methodology: This cross-sectional study was conducted as operational research in five districts of Assam, selected based on zonal representation; between Sept’2021- Aug’2022. Standard format (GOI) was used for VHSND monitoring. Descriptive analysis was done along with quarter-wise comparison of observations and knowledge of Auxiliary Nurse and Midwife (ANM). Results: A total of 370 VHSND sessions were observed. VHSND micro plan availability increased from 87.5% to 98.4% over four quarters. Displaying banners varied between 56.3% and 79.5%, and functional toilets increased from 41.3% to 77%. Height measurement improved from 58.8% to 88.5%. Haemoglobin estimation varied between 46.3% and 75.4%. Recognition of high-risk pregnancies due to severe anaemia increased from 60% to 91.8%. Regarding danger signs like bleeding from vagina increased from 50.0% to 95.1%. Conclusion: Notable progress could be documented in logistical readiness and ANM knowledge in different quarters in post-pandemic period. While service delivery and ANM counselling efforts have seen improvement, targeted interventions remain crucial for optimizing maternal and child health outcomes in the region.